2019
DOI: 10.1111/ecc.13054
|View full text |Cite
|
Sign up to set email alerts
|

Stress and other factors associated with colorectal cancer outpatients with temporary colostomies

Abstract: This study investigated stress and other factors associated with colorectal cancer (CRC) outpatients with temporary colostomies in Taiwan. Temporary colostomies have been incorporated as a defecation alternative to maintain physical function and are accompanied by chemotherapy/radiotherapy in CRC patients. A cross‐sectional study was conducted, and a convenience sampling approach was adopted to recruit 110 discharged CRC patients with temporary colostomies from a medical centre in southern Taiwan. The mean sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…This study is in line with research conducted by Tseng et al that 37% of patients with a stoma reported that they often felt uncomfortable with a colostomy because they felt that their body was incomplete, and was afraid that others would find out that they had a stoma. They were worried that the stoma bag would suddenly fall off (13) .…”
Section: Discussionmentioning
confidence: 99%
“…This study is in line with research conducted by Tseng et al that 37% of patients with a stoma reported that they often felt uncomfortable with a colostomy because they felt that their body was incomplete, and was afraid that others would find out that they had a stoma. They were worried that the stoma bag would suddenly fall off (13) .…”
Section: Discussionmentioning
confidence: 99%
“…7 Research has shown that patients with ostomies feel anxious, panicked, helpless, and stressed to the extent that they are reluctant to participate in normal social activities. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 70% of patients with ostomies develop complications such as stoma infection, bleeding, and stricture due to improper stoma care 7 . Research has shown that patients with ostomies feel anxious, panicked, helpless, and stressed to the extent that they are reluctant to participate in normal social activities 8,9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with psychological discomfort to surgical treatment will produce cancer-induced fatigue in the long run, which will harm the prognosis. Therefore, nursing intervention is essential for patients with radical colorectal cancer surgery (4,5). By informing perioperative matters needing attention and nursing methods, conventional nursing is universal and blind.…”
Section: Introductionmentioning
confidence: 99%